INFLUENCE OF EDUCATIONAL SUPPORT ON ACADEMIC PERFORMANCE OF ORPHANS AND VULNERABLE CHILDREN IN PUBLIC PRIMARY SCHOOLS IN KALAMA SUB COUNTY, MACHAKOS COUNTY, KENYA - Karimi, Kirima Lucy; Maingi, Stephen Mbai (Machakos University, 2019)
Education gives children hope for life and work, and a strong protector against HIV to which Orphans and Vulnerable Children may be particularly susceptible. Despite the Kenyan government effort in mobilising and supporting community based interventions and ensuring access for Orphans and Vulnerable Children to essential services including but not limited to education, health care, psychosocial support and legal protection, OVC in Machakos County and especially Kalama Sub County have been experiencing challenges in meeting their psychosocial, nutritional, academic and health care needs. The purpose of the study was to establish the influence of educational support on academic performance of OVC in public primary schools in Kalama Sub County in Machakos County, Kenya. The study objectives were to examine the influence of class teacher’s individualized support of OVC learning, to assess the influence of the school provision of OVC feeding programme and to establish the influence of teacher’s/caregiver cooperation on OVC academic performance in Kalama Sub County. The study was premised on Abraham Maslow hierarchy of needs motivational theory. The study adopted descriptive survey design. The study sampled 36 teachers and 11 head teachers. The study data was collected through class teachers’ questionnaire and head teachers interview schedule. Content and construct types of validity were ascertained through scrutiny by a panel of university lecturers. Using test retest technique, teachers; questionnaire was found to have a reliability coefficient of 0.78. Both descriptive and inferential statistics were used to analyze the data. The study’s three formulated null hypotheses were analyzed using multiple regression analysis. School provision of OVC feeding programme had the most significant relative contribution to the prediction of pupils’ academic performance (β = 0.578) followed by level of teachers’ individualized support (β = 0.452) while teacher/caregiver’s cooperation had the least influence (β = 0.329). The study recommended that all the School Management Commitees in collaboration with head teachers should be proactive and start income generating programmes in order to support the home grown school food programme in situations when the government stipend is not forthcoming and when it is inadequate. Further, the SMC should collaborate with local community welfare groups and the larger community in order to extend the food programme to the OVC families
Keywords: Academic Performance; Educational Support; Orphan; Vulnerable children; School Feeding Program; Home-Grown School Feeding